MODELING OF HEATING TOPSOIL PARALLEL UPLOADED LINEAR HEAT SOURCE - , А. Я., В. П., Є. В. (Municipal economy of cities (Technical science), 2013)
The formulas for calculating the temperature field horizontal stripes soil heated placed parallel linear heat sources found optimal distance between them and the depth of the conditions for setting the required temperature of the soil.